SOSIALISASI APLIKASI SAMBARA DALAM PENERAPAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR - Fasha, Tegar Adil; Sulastri, Tuti; Rofieq, Ainur (An-Nizam, 2024)
Samsat Mobile West Java (SAMBARA) is part of digital government as the use of digital and information technology is used to motivate the government to be operationally efficient. Samsat Mobile West Java based on digital applications for public services in the vehicle tax payment sector has a positive impact on increasing speed, convenience, practicality so that taxpayers are easy to get vehicle tax information. The community service method applies community education through socialisation to make it more relevant to the topic of service activities. The results of community service have a positive impact that the Sambara application is quite easy to understand, but there are still obstacles when making the payment process via mobile bank. so that tax payments based on the Sambara application are currently not efficient. With this work program, it can help the community from all aspects, whether it is material, time or energy and can also help or support the digitalisation program provided by the government.